REKONSTRUKSI PEMBANGUNAN DI ERA DIGITAL MELALUI TATA KELOLA DIGITAL KOLABORATIF ADAPTIF - Nuriwa Putri Utami; Fani Permata Gusni; Qhazan Wahyu Hariandi; Boni Saputra (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Digital transformation has become a strategic agenda in public governance reform, but various emerging approaches still tend to be partial because they separate the dimensions of institutional adaptivity, multi-actor collaboration, and the use of digital technology into different analytical frameworks. This separation creates limitations in explaining how institutions, actors, and technology interact simultaneously to generate public value in the digital era. This study aims to develop a more comprehensive conceptual framework through the Adaptive-Collaborative Digital Governance (ACDG) model to explain the relationship between institutional adaptivity, multi-actor collaboration, data integration, and public value creation. The study used a Systematic Literature Review (SLR) approach with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature was obtained from Scopus, Web of Science, and Google Scholar databases through a process of identification, screening, eligibility evaluation, and thematic synthesis of articles that met the inclusion criteria. The results show that institutional adaptivity plays a role as a foundation for digital governance transformation through policy flexibility, organizational learning capacity, and the ability to respond to change. Multi-actor collaboration serves as a transformational mechanism linking adaptive capacity with innovation and resource integration, while data interoperability serves as a strategic link enabling evidence-based decision-making. The interaction of these three dimensions generates public value, reflected in improved public service quality, transparency, accountability, public participation, and public trust. The primary contribution of this research is the development of the ACDG model, a new conceptual framework that integrates adaptive governance, collaborative governance, and digital governance perspectives into a single, cohesive model to support more adaptive, collaborative, and sustainable digital governance.